Immunological outcomes between Tenofovir versus Zidovudine-based regimens: a retrospective cohort study - Meshack Lugoba1; Manase Kilonzi1; George M Bwire2; Pacifi que Ndayishimiye1; Wigilya P Mikomangwa1; Hamu J Mlyuka1; Alphonce I Marealle1; Ritah F Mutagonda1; Kennedy D Mwambete2 (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Background: Since 2013, Tenofovir (TDF) and Zidovudine (AZT) based regimen are alternatively used as a fi rst line for treatment of HIV in Tanzania. CD4+ cells count, which is recommended after every six months monitors the immunological progression, and used as one of the indicators of treatment progression. However, there is little literature available information to compare the immunological outcomes of these two regimens. Methods: A hospital-based retrospective cohort study was conducted at Muhimbili National Hospital, Care and Treatment Clinic (MNH-CTC) in Dar es Salaam. HIV/AIDS patients' fi les of October 2012 through November 2016 were reviewed. Using statistical package for social sciences (SPSS version 23), the mean CD4+ cells count were compared by independent t-test while Chi-square test was performed to associate categorical variables. Binary logistic regression was used to control variables such as sex and body mass index (BMI). The results were considered having statistical signifi cance when the P 0.05.